Mental (ill-)health of Swiss elite athletes - Philipp Röthlin; Nadja Ackeret; Daniel Birrer; Claudio Peter; Stephan Horvath (Bern Open Publishing, 2023)
Mental health encompasses both mental health problems and well-being (Uphill et al., 2016). In recent years, world-renowned athletes, including Simone Biles, Michael Phelps, and Naomi Osaka, have directed public attention to the issue of mental health in elite sport by talking openly about their own problems in this regard. Empirical data on levels of well-being and the extent of common mental disorders among current Swiss elite athletes is limited, as previous studies were based on small samples and confined to certain age groups, sports, and/or a single disorder and did not include well-being (e.g., Gerber et al., 2022). In addition, the efforts of Swiss sport federations to support or promote athletes' mental health have not been investigated or evaluated. A representative sample of Swiss athletes (N = 1003, Mage = 21.69, SDage = 7.09, 54% women, 37% team sports, 10% injured) answered questions about symptoms of mental health problems (i.e., PHQ-9, GAD7, SCOFF, ASSQ; Bender et al., 2018; Hill et al., 2010; Kroenke et al., 2001; Spitzer et al., 2006) and their well-being (MHC-SF). We also asked about the extent of basic need satisfaction (Heissel et al., 2018) and perceived organizational support. Overall, the numbers on symptoms of mental health problems (17% depression, 10% anxiety, 22% eating disorders, 18% sleep disorders) and well-being are comparable to other elite sport samples (Reardon et al., 2019) and the general Swiss population. However, we found large group differences. For example, 52% of women athletes were affected by at least one mental disorder symptom, compared with 30% of men athletes. Injured athletes were most affected in terms of depressive symptoms (28%). The study also shows that need satisfaction and frustration in conjunction with demographic factors is related to well-being and symptoms of mental health problems. Furthermore, the more support athletes perceive from their federations, the better their mental health. We conclude that a substantial proportion of athletes are affected by mental problems and more measures are needed to improve this situation, for example through supporting need satisfaction in the sport setting. References Bender, A. M., Lawson, D., Werthner, P., & Samuels, C. H. (2018). The clinical validation of the athlete sleep screening questionnaire: An instrument to identify athletes that need further sleep assessment. Sports Medicine-Open, 4, Article 23. https://doi.org/10.1186/s40798-018-0140-5 Gerber, M., Lang, C., Brand, S., Gygax, B., Ludyga, S., Müller, C., Ramseyer, S., & Jakowski, S. (2022). Perceived recovery and stress states as predictors of depressive, burnout, and insomnia symptoms among adolescent elite athletes. Sports Psychiatry. Advance online publication. https://doi.org/10.1024/2674-0052/a000017 Heissel, A., Pietrek, A., Flunger, B., Fydrich, T., Rapp, M. A., Heinzel, S., & Vansteenkiste, M. (2018). The validation of the German Basic Psychological Need Satisfaction and Frustration Scale in the context of mental health. European Journal of Health Psychology, 25(4), 119-132. https://doi.org/10.1027/2512-8442/a000017 Hill, L. S., Reid, F., Morgan, J. F., & Lacey, J. H. (2010). SCOFF, the development of an eating disorder screening questionnaire. International Journal of Eating Disorders, 43(4), 344-351. https://doi.org/10.1002/eat.20679 Kroenke, K., Spitzer, R. L., & Williams, J. B. (2001). The PHQ‐9: Validity of a brief depression severity measure. Journal of General Internal Medicine, 16(9), 606-613. https://doi.org/10.1046/j.1525-1497.2001.016009606.x Reardon, C. L., Hainline, B., Miller Aron, C., Baron, D., Baum, A. L., Bindra, A., Budgett, R., Campriani, N., Castaldelli-Maia, J. M., Currie, A., Derevensky, J. L., Glick, I. D., Gorczynski, P., Gouttebarge, V., Grandner, M. A., Han, D. H., McDuff, D., Mountjoy, M., Polat, A., Purcell, R. . . . Engebretsen, L. (2019). Mental health in elite athletes: International Olympic Committee consensus statement (2019). British Journal of Sports Medicine, 53(11), 667-699. https://doi.org/10.1136/bjsports-2019-100715 Spitzer, R. L., Kroenke, K., Williams, J. B., & Löwe, B. (2006). A brief measure for assessing generalized anxiety disorder: The GAD-7. Archives of Internal Medicine, 166(10), 1092-1097. https://doi.org/10.1001/archinte.166.10.1092